Coping with constraints: Agentic strategies in the micro-practices of independent adult sex workers in their relations with clients - Sauve, Genevieve (University of Ottawa (Canada), 2004)
Issues of structural constraint and personal agency permeate the discourses of sex workers concerning their everyday practices in sex work, specifically surrounding their interactions with clients. While it appears fruitful and meaningful to respect and value the agency, experiences, and skills of sex workers, their actions remain in part constrained and contextualized by (material and symbolic) structural forces. Nonetheless, sex workers deploy agentic strategies in order to maximize their well-being within sex work. This study is based on qualitative interviews with 12 independent adult female sex workers in Ottawa and Toronto, who work in two settings (street and in-call). Different strategies (individual and collective) are identified and discussed, surrounding the sex worker/client interaction. Eight dimensions are specifically examined: makeup of the clientele, solicitation, contractual terms, pricing, location, boundaries, payment and bad dates. Women's reflective capacities as agents are demonstrated through their articulations of the justifications for actions surrounding their working practices.
Keywords: Sociology, General.